2023
DOI: 10.3390/life13030689
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Histoplasmosis: A Descriptive Review, 2001–2021

Abstract: Gastrointestinal histoplasmosis (GIH) is infrequently described in people without underlying HIV infection. We aimed to compare the clinical presentation of GIH in people with and without HIV infection. We conducted a literature search of published cases of GIH from 2001–2021 and found 212 cases. Of these, 142 (67.0%) were male, and 124 (58.5%) had HIV infection. Most cases were from North America (n = 88, 41.5%) and South America (n = 79, 37.3%). Of the 212 cases, 123 (58.0%) were included in both clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 127 publications
2
12
0
4
Order By: Relevance
“…Nonetheless, the diagnostic confirmation was obtained from the histological examination of the biopsies or resected colonic specimens. Ekeng et al 47 conducted a descriptive review of gastrointestinal histoplasmosis from 2001 to 2021. Of the included 123 cases, 109 (88.6%) were diagnosed by histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the diagnostic confirmation was obtained from the histological examination of the biopsies or resected colonic specimens. Ekeng et al 47 conducted a descriptive review of gastrointestinal histoplasmosis from 2001 to 2021. Of the included 123 cases, 109 (88.6%) were diagnosed by histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological and histopathological findings of endoscopic biopsies of patients undergoing investigation for inflammatory bowel disease (IBD) can mimic the findings of patients with GIH leading to misdiagnosis. 1 For those patients diagnosed with GIH, outcomes were positive in all cases treated with combination amphotericin B/azole and were positive in 96.6% of cases treated with azole monotherapy. 1 A review performed by Kauffman discussed that disseminated histoplasmosis is commonly found in the gastrointestinal tract during autopsy in previously asymptomatic or minimally symptomatic patients.…”
mentioning
confidence: 94%
“…1 For those patients diagnosed with GIH, outcomes were positive in all cases treated with combination amphotericin B/azole and were positive in 96.6% of cases treated with azole monotherapy. 1 A review performed by Kauffman discussed that disseminated histoplasmosis is commonly found in the gastrointestinal tract during autopsy in previously asymptomatic or minimally symptomatic patients. In symptomatic patients, the large bowel is the most common site of involvement with lesser involvement in the small bowel.…”
mentioning
confidence: 94%
See 2 more Smart Citations